Pharmacokinetics of 7,8-dihydroxyflavone in neonatal mice with hypoxia-ischemia related brain injury - Lim, Sin Yin; Scarlett, Cameron O.; Yapici, Sefer; Ferrazzano, Peter; Cengiz, Pelin (Frontiers in Pharmacology, 2025)
Introduction7,8-Dihydroxyflavone (7,8-DHF) is a promising translational therapy in several brain injury models, including the neonatal hypoxia-ischemia (HI) model in mice. However, the neuroprotective effect of 7,8-DHF was only observed in female, but not male, neonatal mice with HI brain injury. It is unknown whether HI-induced physiological changes affect brain distribution of 7,8-DHF differently for male versus female mice. We aimed to evaluate the impact of sex on the pharmacokinetics of 7,8-DHF in plasma and brain neonatal mice following experimentally induced HI brain injury.MethodsLeft-sided HI brain injury was induced in postnatal day 9 (P9) mice, followed by a 5 mg/kg intraperitoneal injection of 7,8-DHF. A liquid chromatography-tandem mass spectrometry method was developed to quantitate the drug concentration in plasma samples, as well as in samples from the left and right brain hemispheres. A nonlinear mixed-effects model was used to analyze the plasma and brain concentration-time data. A semi-quantitative approach was used to evaluate the concentrations of two active O-methylated metabolites of 7,8-DHF (8H7M-flavone and 7H8M-flavone) in both plasma and brain samples.ResultsOur PK analyses show that plasma 7,8-DHF concentrations followed a two-compartment PK model, with more than 95% eliminated by 3 h after the IP injection. Sex was not significantly associated with the PK of 7,8-DHF; however, HI brain injury was associated with a 21% reduction in clearance (p < 0.01). The distribution of 7,8-DHF to the brain was rapid; however, the extent of brain distribution was low with the right and left brain-to-plasma partition coefficients being 8.6% and 9.9%, respectively. Additionally, both O-methylated metabolites of 7,8-DHF were detected in the plasma and brain.ConclusionThe plasma and brain PK of 7,8-DHF in neonatal mice were similar between males and females. The low extent of 7,8-DHF brain distribution and the potential effects of the active metabolites should be considered in future studies evaluating the therapeutic effects of 7,8-DHF.